Alveolar Bone Loss in Adult Young Patient Seeking Periodontal Treatment (Radiographic Study) (Mustansiria Dental Journal, 2018)
Thorough clinical and radiographic examination is necessary to detect, evaluateand diagnose periodontal disease. The aim of present study is to evaluate interdentalbone loss in patients with chronic adult periodontitis radiographically. One hundredeighty sites (for maxillary anterior teeth only) were examined for type and severity ofalveolar bone loss. The results reveal that 80% of all examined sites had differentseverity of bone loss. Mild bone loss was more frequent than Moderate or Severe andhorizontal more than vertical or angular bone loss. Interdental bone between centraland lateral incisors was the most affected site in this study.